2010
DOI: 10.1007/s00259-009-1370-z
|View full text |Cite
|
Sign up to set email alerts
|

PET imaging of HER1-expressing xenografts in mice with 86Y-CHX-A″-DTPA-cetuximab

Abstract: Cetuximab is a recombinant, human/mouse chimeric IgG1, monoclonal antibody (mAb) that binds to the epidermal growth factor receptor (EGFR/HER1). Cetuximab is approved for the treatment of patients with HER1-expressing metastatic colorectal cancer. Limitations in currently reported radiolabeled cetuximab for PET applications prompted the development of 86Y-CHX-A”-DTPA-cetuximab as an alternative for imaging HER1-expressing cancer. 86Y-CHX-A”-DTPA-cetuximab can also serve as a surrogate marker for 90Y therapy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
97
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(101 citation statements)
references
References 30 publications
(44 reference statements)
2
97
2
Order By: Relevance
“…The usefulness of cetuximab was also confirmed in a study in which cetuximab labeled with 86 Y was studied for positron-emission tomography (PET) imaging. 24,25 The studies described herein are both exploratory and confirmatory to the above hypothesis, evaluating the potential of cetuximab for a-targeted therapy of disseminated intraperitoneal disease. Consistent with previous studies from this laboratory, this investigation also includes studies combining chemotherapeutics (gemcitabine and carboplatin) with RIT to assess potential therapeutic efficacy enhancement of HER1 targeting a-emitting high-LET 212 Pb-labeled cetuximab.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…The usefulness of cetuximab was also confirmed in a study in which cetuximab labeled with 86 Y was studied for positron-emission tomography (PET) imaging. 24,25 The studies described herein are both exploratory and confirmatory to the above hypothesis, evaluating the potential of cetuximab for a-targeted therapy of disseminated intraperitoneal disease. Consistent with previous studies from this laboratory, this investigation also includes studies combining chemotherapeutics (gemcitabine and carboplatin) with RIT to assess potential therapeutic efficacy enhancement of HER1 targeting a-emitting high-LET 212 Pb-labeled cetuximab.…”
Section: Introductionmentioning
confidence: 94%
“…[21][22][23][24]26,[35][36][37][38] Cetuximab has been the focus of several imaging studies with the objective of assessing the value of this mAb for disease monitoring, HER1 expression and distribution, patient selection and for performing dosimetric calculations. [23][24][25][26] The preclinical studies from this laboratory demonstrated excellent targeting of s.c. tumor by 111 In-cetuximab given intravenously. 23 Targeting was obtained in 5 tumor models (2 colorectal, 1 prostate, 1 pancreatic and 1 ovarian), determined by direct quantitation of tissues and by planar g-scintigraphy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of natural ligands is limited by their physiological activity that can provoke adverse reactions: nausea, vomiting, diarrhea, hypotension, fever and chills (17). Intact mAbs demonstrated their capacity to image EGFR-expressing tumors (18)(19)(20) but the sensitivity of such tracers can be limited by the long biodistribution times, slow tumor penetration, and slow blood clearance of the tracers, which reduces target or non-target contrast. The affibody molecules, a new class of imaging agents combine small size of natural ligands, absence of physiological action, and high affinity to target and can be used for radioimmuno-diagnostic.…”
Section: Introductionmentioning
confidence: 99%